Effect of Al2O3 sandblasting particle size on the surface topography and residual compressive stresses of three different dental zirconia grades - Kim, Hee Kyung; Ahn, Byungmin (Materials, 2021)
This study investigated the effect of sandblasting particle size on the surface topography and compressive stresses of conventional zirconia (3 mol% yttria-stabilized tetragonal zirconia pol-ycrystal; 3Y-TZP) and two highly translucent zirconia (4 or 5 mol% partially stabilized zirconia; 4Y-PSZ or 5Y-PSZ). Plate-shaped zirconia specimens (14.0 × 14.0 × 1.0 mm3, n = 60 for each grade) were sandblasted using different Al2O3 sizes (25, 50, 90, 110, and 125 μm) under 0.2 MPa for 10 s/cm2 at a 10 mm distance and a 90° angle. The surface topography was characterized using a 3-D confocal laser microscopy and inspected with a scanning electron microscope. To assess residual stresses, the tetragonal peak shift at 147 cm−1 was traced using micro-Raman spectroscopy. Al2O3 sandblasting altered surface topographies (p < 0.05), although highly translucent zirconia showed more pro-nounced changes compared to conventional zirconia. 5Y-PSZ abraded with 110 μm sand showed the highest Sa value (0.76 ± 0.12 μm). Larger particle induced more compressive stresses for 3Y-TZP (p < 0.05), while only 25 μm sand induced residual stresses for 5Y-PSZ. Al2O3 sandblasting with 110 μm sand for 3Y-TZP, 90 μm sand for 4Y-PSZ, and 25 μm sand for 5Y-PSZ were considered as the recommended blasting conditions.
Keywords: Blasting conditions; Confocal laser microscopy; Micro Raman Spectroscopy; Partially stabilized zirconia; Peak shift; Residual compressive stress; Yttria stabilized tetragonal zirconias; Air abrasion; Dental stress analysis; Phase transition; Surface properties; Zirconium oxide